Research handbook on intellectual property and employment law - Bruun, Niklas; Mansala, Marja-Leena (Research handbooks in intellectual property series, 2021)
"This comprehensive Research Handbook explores the rights of employers and employees with regard to intellectual property (IP) created within the framework of the employment relationship. Investigating the development of employee IP from a comparative perspective, it contextualises issues in the light of theoretical approaches in both IP law and labour law. Leading academic experts examine the most crucial building blocks of the regulation of employee IP, such as authorship, inventorship and creatorship, as well as individual, corporate and collective works. Chapters focus on US and European law, but also offer insights from Chinese, Japanese and Korean law. The Research Handbook also tackles new and developing global challenges in the field, including labour mobility, trade secrets, non-compete clauses, university employees, cross-border business matters, and choice of law issues. Scholars and students in both IP and labour law, and particularly those working at the intersection of these fields, will find this Research Handbook invaluable. It will also provide important insights for legislators, business practitioners and university management"--